Pengaruh Kemampuan Teknis, Kemampuan Manajerial, Kemampuan Perilaku dan Kemampuan Konseptual Terhadap Kinerja Karyawan PT. Telkom Cabang Kuala Kapuas - Marlina Kasyfiatie; Rasyidi Rasyidi; Taharuddin Taharuddin (Universitas Lambung Mangkurat, 2016)
The aims of the study ware to identify and analyze how much the influence of Technical Ability, Managerial Ability, Conceptual Ability and Behavioural Ability which partially and simultaneously measured to the performance of employees of PT. Telkom Kuala Kapuas Branch.This research used quantitative approach with associative research type and the location for the research was is at. PT. Telkom Kuala Kapuas Branch. The population was all employees of the company with a total sample of 26 respondents. The research applied multiple linear regression techniques for data analysis with a significant level of 0:05.The results of this study demonstrated that partially, there was a significant effect of technical ability to the employee performance at 0,121; the managerial ability at 0.332; the behavioural ability at 0.519; and the conceptual ability at 0.187; to the employees performance. Meanwhile, simultaneously, there was a significant effect of technical ability, managerial ability, conceptual ability and behavioral ability to the employees performance of PT. Telkom Kuala Kapuas Branch of 0.575. Keywords: Performance, Ability, Technical, Managerial, Behavioral, Conceptual.